Emotional stress in the aetiology of cancer - Hamilton, James (British Homeopathic Journal, 1972)
1 This paper is based on a study of sixteen patients suffering from various forms of cancer. These patients were found in general practice.2 In these patients the malignant disease was found in breasts, stomach, colon, rectum, uterus, larynx and lungs.3 It was found that these sixteen patients had histories of both somatic and psychological illnesses for varying periods before the presence of cancer was detected. None had a clean bill of health before the onset of cancer.4 A study and assessment of the personalities of the patients were made. These referred to the periods before and during the development of cancer.5 The presence of psychological symptoms resulting from emotional stress previous to the development of cancer was noted in all cases.6 It was noted that in many patients, the symptoms of cancer developed gradually and were aggravated during periods of severe emotional distress.7 The psychological stress produced symptoms predominantly related to fear, anxiety, apprehension, grief and depression, anger and resentment.8 The hypothesis that, from a study of these sixteen patients, cancer may have the characteristics of a psychosomatic disease, was explored.9 It would appear from the evidence of these cases that a more detailed scientific study of cancer cases would be profitable, to asses with greater precision the hypothesis that unpleasant emotional stress plays a part in the aetiology of at least some forms of cancer.